PAR Conversion Efficiency of Pigeonpea (Cajanus cajan (L) Mill sp.) With Different Intercrops and Levels of Fertilizers - Patel, H R; Mehta, A N (Annals of Arid Zone, 2016)
Studies on PAR conversion efficiency under different levels of fertilizer application, showed that the grain yield of pigeonpea and pigeonpea equivalent in cropping system was found to be significant, while fertilizer treatments remained non- significant. The PAR efficiency in intercropped pigeonpea was low during early growth and harvest stages of intercrop, but the same was accelerated with canopy development during reproductive stage. The conversion efficiency of sole pigeonpea, during reproductive stage remained more or less constant resulting in highest straw and lowest grain yield. An overall conversion efficiency of component crops in pigeonpea + groundnut, pigeonpea + cowpea, pigeonpea + greengram and pigeonpea + blackgram cropping systems were superior over others for yield stability and monetary returns.